Relativistic RPA for isobaric analogue and Gamow-Teller resonances in closed shell nuclei - De Conti, C. [UNESP]; Galeão, A. P. [UNESP]; Krmpotić, F. (Elsevier, 1998)
We perform a self-consistent relativistic RPA calculation for the isobaric analogue and Gamow-Teller resonances based on relativistic mean field theory results for the ground states of 48Ca, 90Zr and 208Pb. We use the parameter set NL1 for the σ, ω and ρ mesons, and experimental values for the pion and nucleon. An extra parameter, related to the intensity of the contact term in the pion-exchange interaction, is crucial to reproduce the latter resonances. © 1998 Published by Elsevier Science B.V. All rights reserved.